2019
DOI: 10.3390/microorganisms7030071
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis DSM 32315 Supplementation Attenuates the Effects of Clostridium perfringens Challenge on the Growth Performance and Intestinal Microbiota of Broiler Chickens

Abstract: The objective of this study was to evaluate the effects of the dietary supplementation of Bacillus subtilis DSM 32315 (probiotic) on the performance and intestinal microbiota of broiler chickens infected with Clostridium perfringens (CP). One-day-old broiler chickens were assigned to 3 treatments with 8 replicate pens (50 birds/pen). The treatments were: non-infected control; infected control; and infected supplemented with probiotic (1 × 106 CFU/g of feed). On day of hatch, all birds were sprayed with a cocci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Based on the predictive microbial function analysis of microbiota by PICRUSt, the metabolic pathways related to methane metabolism, transcription machinery, purine metabolism and protein export were enriched by heat-inactivated compound probiotics. Similar work on broilers revealed that live probiotic supplementation modulated the diversity and composition of ileal and cecal microbiota, and enriched pathways involved in carbohydrate metabolism whereas decreasing pathways of protein metabolism (Bortoluzzi et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Based on the predictive microbial function analysis of microbiota by PICRUSt, the metabolic pathways related to methane metabolism, transcription machinery, purine metabolism and protein export were enriched by heat-inactivated compound probiotics. Similar work on broilers revealed that live probiotic supplementation modulated the diversity and composition of ileal and cecal microbiota, and enriched pathways involved in carbohydrate metabolism whereas decreasing pathways of protein metabolism (Bortoluzzi et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…In a C. perfringens/Eimeria maxima coinfection model of avian necrotic enteritis, feeding of B. subtilis reduced gut pathology and animal mortality, and restored alterations in the intestinal microbiome, compared with controls (22). Other studies have confirmed the ability of Bacillus DFMs to reduce C. perfringens colonization of the intestinal mucosa and improve animal growth performance in avian necrotic enteritis (36)(37)(38)(39)(40)(41). In general, while the beneficial effect of Bacillus DFMs on body weight gains in healthy, uninfected chickens is generally moderate (<10%), a more pronounced outcome of the dietary supplements has been observed when weight loss is aggravated as a consequence of pathogenic infection (42).…”
Section: Discussionmentioning
confidence: 91%
“…perfringens , either directly or via promoting growth of other bacterial species that may competitively exclude Clostridia . Relative abundance of Bacteroides in the ileal digesta of broiler chickens increases with NE challenge ( Bortoluzzi et al., 2019 ). Bacteroides and Prevotellaceae can degrade mucus oligosaccharides, which results in the disruption of intestinal mucosal barrier, thus causing intestinal inflammation ( Rho et al., 2005 ; Berry et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%